Efektivitas Penyelenggaraan Pelayanan Publik (Perizinan) Sistem Satu Pintu di Kabupaten Ponorogo - Dwi Caksono, Cipto; Pradana, Intan; Pu’ah, Dewi; Wahjuni Djuwita Ningsih, Ekapti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2024)
During a pandemic like this time that hit almost all over the world, including in Indonesia. The existence of a pandemic has limited the space for public activity to move, so that the government is encouraged to make new policies or innovations in the field of public services that are better for the benefit of the wider community. In addition, the Revolutionary Era also demands the advancement of data and information systems in public services, the current pandemic period provides momentum for the government to innovate in the field of public services. One of themis the one-door integrated service system or one-door service, where the community can carry out activities related to administration and licensing in one place without having to go here and there and save time and energy. This study uses a qualitative method. This research also shows that the government has made various innovations in the field of public services.